Mid‐Latitude Ionospheric Response to a Weak Geomagnetic Activity Event During Solar Minimum. Issue 1 (20th January 2023) - Zhai, Changzhi; Cai, Xuguang; Wang, Wenbin; Coster, Anthea; Qian, Liying; Solomon, Stanley C.; Yu, Tingting; He, Maosheng
Abstract: Salient depletions (30%–40% of the reference values) were observed in the vertical total electron content (VTEC) from the Global Navigation Satellite System (GNSS) network and the topside ionosphere electron density from Swarm satellites measurements over the Western Atlantic and Northeast American regions during a weak geomagnetic activity event (maximum Kp = 2.3) between Day‐of‐Year (DOY) 155 and 156 in 2019. These depletions coincided with thermospheric Oxygen (O) to Nitrogen (N2 ) column density ratio (∑O/N2 ) depletions observed by the Global‐scale Observations of the Limb and Disk (GOLD) mission. The National Center for Atmospheric Research (NCAR) Thermosphere–Ionosphere–Electrodynamics General Circulation Model (TIEGCM) reproduces VTEC depletions qualitatively, which is used to investigate the underlying mechanisms. Term analysis of the TIEGCM oxygen ion ( O + ) continuity equation showed that the VTEC depletion was dominated by chemical processes and neutral wind transport effects, which were partially offset by the transport due to E × B drifts and ambipolar diffusion. On the dayside, the contribution from the neutral wind transport was induced by a weak poleward meridional wind during the geomagnetic activity. With the decrease of electron density, the loss rate in the chemical term was reduced, which led to a large reduction of the contribution from chemical processes to electron density and TEC changes during the event, and the contribution of the neutral wind to VTEC depletion even exceeded that of chemical processes after 14:10 UT. Key Points: Thirty percentage VTEC depletions in mid‐latitude were observed during a weak geomagnetic activity event with a maximum Kp of 2.3 Neutral wind transport played a more important role in generating the VTEC depletions than the chemical processes The impact that the weak geomagnetic activity brings on mid‐latitude ionosphere cannot be simply ignored